Dynamics of social capital among fair trade and non-fair trade coffee farmers - Bautista, Reynaldo A. (Animo Repository, 2018)
Fair trade (FT), a movement that aims to set fair prices for products, alleviate poverty, and assist producers marginalized by the traditional economic model, lends itself to investigation through social capital (SC) lens as SC sits within the network theory area of management literature. The primary contribution of this paper is the analysis of whether FT impacts the dynamics of the different SC dimensions. This study used both quantitative and qualitative techniques. I surveyed 97 farmers from Atok (fair trade supplier) and 96 farmers from Tublay (non-fair trade supplier). Also, I conducted focus group discussions of 8 to 10 members from each group and in-depth interviews with formal and informal leaders and key-informants (buyer and local government leaders). The t-test revealed that the farmer cooperative that supplies to FT organization has a significantly higher tendency to ask support from non-government organizations (NGO) and financial institutions. Likewise, they have a higher score in collective action and perceived economic performance. Additionally, regression analysis showed that trust in local government unit (LGU), empowerment, and cooperative classification are positive predictors of perceived economic performance while trust in NGO and membership expansion have negative effects on perceived economic performance. © 2018 by De La Salle University.